THE EFFECTIVENESS OF EXPERIENTIAL LEARNING THROUGH JELAJAH ALAM SEKITAR (JAS) APPROACH ON THE NINTH-GRADE STUDENTS’ COGNITIVE LEARNING OUTCOMES AND ACTIVENESS ON THE FUNCTION OF SOIL FOR LIFE AND ITS COMPONENTS LEARNING MATERIAL - Alief Alfian; Eny Hartatiyati; Ferina Agustini; Theresia Yustina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper discusses the effectiveness of Experiential Learning on the Jelajah Alam Sekitar approach (JAS) on the ninth-grade students’ cognitive learning outcomes and activeness at SMP Negeri 6 Semarang on the function of soil for life and its component learning material. The research uses the Static Group Comparison method by involving two classes. The control class (9H) uses the lecture method and the experimental class (9G) uses the JAS approach based on Experiential Learning. The cognitive learning outcome data were obtained from multiple choice objective tests (summative assessment), while students’ activeness data were obtained from observation sheets. Data were analyzed by using an independent T-test. The results indicate that the JAS approach was effective in improving students’ cognitive learning outcomes and activeness. It is evidenced by a significant difference between the average score of cognitive learning outcomes in the control class at 89 and in the experimental class at 96.3 with a p-value of 0.043. In addition, there was a difference between the average score of students’ activeness in the control class at 12.3 and in the experimental class at 13 with a p-value of 0.116. Yet, the differences were not significant. Based on the results of the research, it is recommended that teachers can use the JAS approach as one of the alternative learning methods that can improve students’ cognitive learning outcomes and activeness.